2010
DOI: 10.1530/eje-10-0288
|View full text |Cite
|
Sign up to set email alerts
|

A hypoechoic pattern of the thyroid at ultrasound does not indicate autoimmune thyroid diseases in patients with morbid obesity

Abstract: Objective: Thyroid ultrasound (US) scan is a valuable tool for diagnosing thyroid diseases. In autoimmune thyroid disease (AITD), an hypoechoic pattern of the thyroid at US is related to circulating thyroid antibodies (Abs). The aim of this study was to evaluate the diagnostic accuracy of thyroid US for the detection of AITD in patients with morbid obesity. Design: Thyroid US scans showing an hypoechoic pattern of the thyroid were collected from 105 morbid obese patients (body mass index (BMI) O40 kg/m 2 ) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 25 publications
8
41
0
1
Order By: Relevance
“…Chiovatto and cols. also evaluated the accuracy of US in detecting autoimmune thyroid diseases in patients with class III obesity, and detected that class III obesity may affect thyroid morphology (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiovatto and cols. also evaluated the accuracy of US in detecting autoimmune thyroid diseases in patients with class III obesity, and detected that class III obesity may affect thyroid morphology (8).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the prevalence of more severe forms of obesity, defined as class III obesity, has been increasing worldwide (1). Over recent years, various publications have focused on the association between insulin resistance (IR) and thyroid abnormalities (2)(3)(4)(5)(6)(7)(8). Causes of thyroid dysfunction are positively associated with IR, not only in subjects diagnosed with diabetes mellitus (DM), but also in subjects without this diagnosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…After weight loss, a reduction in thyroid volume was also observed (60). Studies on children and adults also demonstrated that obesity is associated with a thyroid hypo-echogenic pattern at US, which occurs independently from thyroid autoimmunity (77,78). Indeed, among all patients with a thyroid hypo-echogenic pattern of the gland, only a minority of those with morbid obesity (20%) had serological evidence of thyroid autoimmunity (78).…”
Section: Thyroid Function and Structure In Obese Subjectsmentioning
confidence: 98%
“…Studies on children and adults also demonstrated that obesity is associated with a thyroid hypo-echogenic pattern at US, which occurs independently from thyroid autoimmunity (77,78). Indeed, among all patients with a thyroid hypo-echogenic pattern of the gland, only a minority of those with morbid obesity (20%) had serological evidence of thyroid autoimmunity (78). This figure was in contrast with the much greater prevalence (O80%) of thyroid antibodies in non-obese patients.…”
Section: Thyroid Function and Structure In Obese Subjectsmentioning
confidence: 99%
“…However, these early studies enrolling patients with raised serum levels of TSH did not take into account the presence of clinical conditions associated with an increase in circulating TSH levels recently proven not to be indicative of thyroid failure. In particular, morbid obesity has recently been identified to cause an increase in the serum levels of TSH often associated with the presence of a hypoechoic pattern of the thyroid at US, which do not imply that hypothyroidism is present (24,25,26,27). Taking into account the above concepts, it would be reasonable to assume that the prevalence of SN-CAT might have been overestimated by earlier studies.…”
Section: Discussionmentioning
confidence: 99%